Implementasi Deep Learning melalui Pendampingan Kesehatan Mental Peserta Didik bagi Pemberdayaan Guru Sekolah Dasar - Zumrotus Sa’diyah; Midya Yuli Amreta; Khoirotus Silfiyah; Widya Mufidatul 'Ula; Saskia Agustina; Nurul Khofifah Tunni’mah (GUYUB: Journal of Community Engagement, 2026)
This community service program aims to improve the understanding and skills of elementary school teachers in Ngasem District, Bojonegoro Regency, in recognizing students’ psychological conditions and integrating them into Deep Learning–based instruction. The program involved 174 teachers who are members of the Teacher Working Group (KKG) and was implemented using a participatory mentoring approach consisting of five stages: socialization, training, technology integration, mentoring and evaluation, and program sustainability. The evaluation employed a pretest–posttest design, observation sheets, and assessment rubrics. The instruments included a conceptual understanding test, an early identification rubric for students’ psychological conditions, and an observation sheet for classroom implementation. The results indicate an increase in teachers’ conceptual understanding from 58.5% to 89.25% (an increase of 30.75%), instructional design skills from 64% to 90% (an increase of 26%), and the integration of mental health aspects from 59% to 83.67% (an increase of 24.67%).Early identification skills improved from 55% to 80% (an increase of 25%), as reflected in teachers’ ability to recognize signs of stress, anxiety, and behavioral changes in students. In addition, teachers’ innovative and adaptive attitudes increased from 60.75% to 88% (an increase of 27.25%). These findings demonstrate that KKG-based mentoring is effective in enhancing teachers’ capacity in a measurable way across knowledge, skills, and the implementation of learning practices that are sensitive to students’ mental health